Can Cervical Lymph Node Metastasis Increase the Risk of Distant Metastasis in Papillary Thyroid Carcinoma? - Wang, Wenlong; Ding, Ying; Jiang, Wei; Li, Xinying (Frontiers in Endocrinology, 2022)
Abstract Background: Distant metastasis (DM) is a rare event and has negative effect on prognosis for papillary thyroid carcinoma (PTC), the relationship between cervical lymph node metastasis (LNM) and DM is complicated and unclear. This study aimed to evaluate the impact of N stages subclassification on different distant metastasis sites based on age stratification, especially for patients with papillary thyroid microcarcinoma. Methods: A total of 28712 patients with PTC between 2010 and 2018 were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. Multivariable logistic regression analysis was utilized to adjust confounding variables. Risk stratification including positive lymph nodes number and lymph nodes ratio was established by receiver-operating characteristic (ROC) curves to help to predict DM. Results: Lung was the most common metastatic sites regardless of N0, N1a disease, or N1b disease. As the N stage increased, the higher the rate of DM was identified. After age stratification, only N1b disease significantly increased the risk of LM (OR=20.45, P <0.001) rather than BM (OR=3.46, P >0.05) in younger patients. But in older patients, N1b disease significantly increased the risk of both LM (OR=4.10, P <0.001) and BM (OR=2.65, P=0.007). In patients with PTMC, N1a disease did not increase the risk of DM, LM, and BM compared with N0 disease (P >0.05). Furthermore, Combined N stage with risk stratification has well performance in predicting DM (AUC=0.761). Similar results were shown in PTC patients with LM (AUC=0.770) and BM (AUC=0.729). Conclusion: Overall, the incidence of DM significantly increased with the progress of N disease after age stratification. N1a disease did not increase the risk of DM in PTMC patients, regardless of LM or BM. Combined N stage with risk stratification may be beneficial for DM prediction.